Strategies of Behavior in Conflicts, Coping strategies, and Defense Mechanisms Among Adolescent Boys and Girls - Irina V. Borisova; Yuliya N. Khadykina (Rossijskij psihologičeskij žurnal., 2018)
Introduction. The present paper overviews domestic and foreign studies on conflicts, psychological defense mechanisms, and coping strategies. The novelty of the research lies in studying the relationships among the strategies of behavior in conflicts, coping strategies, and psychological defense mechanisms among adolescent boys and girls. Materials and Methods. These were the Life Style Index questionnaire (R. Plutchik); the Ways of Coping Questionnaire (WCQ) (R. Lazarus); The Thomas–Kilmann Conflict Mode Instrument (TKI). The study involved 23 boys and 16 girls, tenth and eleventh grade secondary school students in Lyubokhna, Bryansk region. Results. The study revealed a statistically significant difference in coping strategies and psychological defense mechanisms in difficult or stressful situations among adolescent boys and girls. The strategy of cooperation in conflict situations had a direct relationship with accepting responsibility and seeking social support in the group of adolescent boys. The strategy of cooperation in conflict situations had an inverse relationship with confrontational coping and self-controlling in the group of adolescent girls. Discussion. Adolescent boys and girls differ in how their strategies of behavior in conflicts are associated with coping strategies and defense mechanisms. The findings are useful for providing psychological assistance to adolescent boys and girls.